Meningkatkan Keterampilan Menulis Karangan Narasi Melalui Model PWIM (Picture Word Inductive Model) Siswa Kelas IV B SD Negeri Ketib Kecamatan Sumedang Utara Kabupaten Sumedang - Gina, Asifa Miftahul; Iswara, Prana Dwija; Jayadinata, Asep Kurnia (Jurnal Pena Ilmiah, 2017)
This research is motivated by low student narrative writing skill. The purpose of the study so that students can write narrative essay using the skeleton essay and the use of capital letters and dots well through the model of learning PWIM. The PWIM model (Picture Word Inductive Model) seeks to improve the narrative writing skill in grade IV B SDN Ketib academic year 2016/2017. The subjects were 22 students of grade IV B. Based on the test results with KKM initial data 66,7 shows that 22 people in writing narrative text only 2 people (9,09%) expressed completely. The remaining 20 people (90.91%) have not been completed. This study was conducted for three cycles. The instruments used were observation, interviews, field notes and tests. The results show that there is an increase in terms of basic ideas, skeletons, and the use of capital letters and dots. Thus, it can be concluded that the application of this PWIM model can improve narrative writing skills in grade IV B SDN Ketib.